A long-term subacute sclerosing panencephalitis survivor treated with intraventricular interferon-alpha for 13 years - Minsun Kwak; Hye-Ryun Yeh; Mi-Sun Yum; Hyun-Jin Kim; Su Jeong You; Tae-Sung Ko (Korean Pediatric Society, 2019)
Subacute sclerosing panencephalitis (SSPE) is a rare, progressive, and fatal central nervous system disorder resulting from persistent measles virus infection. Long-term data are scarce, with a maximum follow-up period of 10 years. Interferon-alpha (IFN-α) is a protein that exerts its antiviral activity via enhancement of cellular immune response and is reported to be an effective drug for the treatment of SSPE. However, there is currently no consensus regarding the optimal duration of IFN-α therapy. Here, we present a case report of a patient with SSPE treated with long-term intraventricular IFN-α therapy, which facilitated clinical improvement and neurological stabilization without causing serious adverse effects. To the best of our knowledge, this is one of the longest follow-up studies investigating a patient with SSPE receiving intraventricular INF-α treatment. Further studies are necessary to validate the benefits and safety of long-term intraventricular IFN-α treatment in patients with SSPE.